PENGARUH IMPLEMENTASI TOTAL QUALITY MANAGEMENT, PARTISIPASI PENYUSUNAN ANGGARAN,TERHADAP KINERJA MANAJERIAL KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING PADA PT. BANK SULSELBAR CABANG MAKASSAR - Tantaka A Tao; Jeny Kamase; Amiruddin Amiruddin (INVOICE : JURNAL ILMU AKUNTANSI, 2021)
The Effect of Implementation of Total Quality Management, Participation in Budgeting, on Managerial Performance, Organizational Commitment as a Moderating Variable at PT. Bank Sulselbar Makassar Branch. This study aims to determine and describe the implication of total quality management, participation in budgeting, in improving management performance as a moderating variable in PT. South and West Sulawesi Bank. This research uses quantitative methods and performs data analysis with statistical procedures. The sampling method used is by using a sampling formula with a sample of 69 respondents. The analytical method used is moderated regression analysis (MIRA) with the help of SPSS version 24.0 for windows. The results of hypothesis testing show that the Total Quality Management (TQM) variable has an effect on managerial performance, that the Budgetary Participation Variable has an effect on managerial performance, that the Total Quality Management (TQM) variable has an effect on managerial performance and the interaction between total quality management (TQM) has influence on managerial performance. Meanwhile, organizational commitment variable does not have a significant effect on the relationship between budgeting participation and managerial performance.Keywords: Total Quality Management, Participation in Budgeting, Managerial Performance, Organizational Commitment, and PT. South and West Sulawesi Bank Makassar Branch.